Psalm 120 and the question of authorship of the songs of Ascents - Amzalag, Nisim 1962- (2021)
As the first of the songs of Ascents, Psalm 120 might be seen as key to understanding the whole corpus, but its content remains poorly understood. This study suggests that its author was a smith-poet committed to the Edomite/Qenite traditional worship of YHWH, here complaining about participating, through the fabrication of iron weapons, in the demise of Edom (553 BCE). On this reading, the poem becomes a lament on the irremediable demise of traditional (metallurgical) Yahwism after the rise of iron metallurgy and its transformation of war. Introducing the Ascents, this song might express the search for an alternative form of Yahwism emancipated from the original metallurgical dimension. Expressed in Israel, this alternative Yahwism becomes praised in the other songs of Ascents. This interpretation corroborates the rise of a group of Edomite poets (Ezrahites) in Jerusalem in the early Persian period and its integration within the temple staff.
Keywords: Psalm 120; early Persian Period; Edom; Ezrahite singers; non-Israelite yahwism; Songs of Ascents